Manufacturing method of solid electrolyte sheet

The described method addresses the issues of wrinkles and bubbles in three-dimensional structures by forming multiple solid electrolyte layers within a three-dimensional structure, ensuring the integrity and safety of the solid electrolyte sheet production process.

JP7625029B2Active Publication Date: 2025-01-31HONDA MOTOR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023059327
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-31
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Conventional methods for manufacturing solid electrolyte sheets face issues such as wrinkles, bubbles, and structural breakage in three-dimensional structures like non-woven fabrics, hindering efficient mass production and safety.

Method used

A method involving coating a first slurry on a substrate, forming a first non-hardened material, drying it to create a first solid electrolyte layer, applying a second slurry on top, and then introducing a three-dimensional structure into a second non-hardened material within the structure, followed by drying to form a second solid electrolyte layer, thereby suppressing wrinkles and bubbles.

Benefits of technology

This method effectively prevents wrinkles and bubbles in three-dimensional structures, ensuring the integrity of the solid electrolyte sheet and enhancing the efficiency and safety of the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625029000001
    Figure 0007625029000001
  • Figure 0007625029000002
    Figure 0007625029000002
  • Figure 0007625029000003
    Figure 0007625029000003
Patent Text Reader

Abstract

To provide a method for producing a solid electrolyte sheet that suppresses wrinkles of a three-dimensional structure such as a nonwoven fabric or bubbles along the structure, as well as, suppresses fracture of the three-dimensional structure.SOLUTION: A method for producing solid electrolyte sheet filled with solid electrolyte comprises: a first step of coating a first slurry containing a solid electrolyte on a substrate to form a first uncured product; a second step of drying the first uncured product on the substrate to form a first solid electrolyte layer; a third step of coating a second slurry on a top face of the first solid electrolyte layer to form a second uncured product; a fourth step of causing a sheet-like three-dimensional structure to enter the second uncured product; and a fifth step of drying the second uncured product which has entered the three-dimensional structure and the second uncured product that is present on the three-dimensional structure to form a second solid electrolyte layer inside and on the three-dimensional structure, and obtaining a solid electrolyte sheet in which the second solid electrolyte layer is filled in the three-dimensional structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a solid electrolyte sheet. [Background technology]

[0002] The solid-state battery is composed of a laminated body in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are laminated. For example, a solid electrolyte sheet filled with a solid electrolyte is used as the solid electrolyte layer. The solid electrolyte sheet includes a sheet-like three-dimensional structure such as a nonwoven fabric, which is disposed at the center in the thickness direction and filled with a solid electrolyte, and a solid electrolyte layer formed so as to cover the front and back surfaces of the three-dimensional structure.

[0003] Conventionally, the three-dimensional structure is immersed in a slurry containing a solid electrolyte, the inside of the three-dimensional structure is filled with the slurry, and the slurry is then dried to form a solid electrolyte sheet. However, this method has problems in that the mass productivity of the solid electrolyte sheet and the safety in its manufacture are poor. In order to ensure the mass productivity and safety in its manufacture, it is necessary to obtain a solid electrolyte sheet having the same quality as that obtained by the method of immersing the three-dimensional structure in the slurry by the method of coating the three-dimensional structure with the slurry.

[0004] In a method of applying the slurry to the three-dimensional structure, the three-dimensional structure can be positioned in the center in the cross-sectional direction by applying the slurry twice, and a method of obtaining a solid electrolyte sheet having the same quality as that obtained by a method of immersing the three-dimensional structure in the slurry is known (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2022-151241 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the conventional technology disclosed in Patent Document 1 had room for improvement, as wrinkles in the three-dimensional structure such as the nonwoven fabric and air bubbles along them could occur, and the three-dimensional structure could be caught in the die coater, causing breakage.

[0007] The present invention provides a method for manufacturing a solid electrolyte sheet that suppresses wrinkles and bubbles along the wrinkles in a three-dimensional structure such as a nonwoven fabric, and also suppresses breakage of the three-dimensional structure, thereby contributing to energy efficiency. [Means for solving the problem]

[0008] In order to achieve the above object, the present invention provides the following means. [1] A method for producing a solid electrolyte sheet filled with a solid electrolyte, comprising the steps of: A first step of applying a first slurry containing a solid electrolyte onto a substrate to form a first uncured material made of the first slurry; a second step of drying the first uncured material on the substrate to form a first solid electrolyte layer; a third step of applying a second slurry to an upper surface of the first solid electrolyte layer to form a second uncured material made of the second slurry; A fourth step of penetrating a sheet-like three-dimensional structure into the second uncured material; a fifth step of drying the second uncured material that has entered the interior of the three-dimensional structure and the second uncured material on the three-dimensional structure to form a second solid electrolyte layer inside the three-dimensional structure and on the three-dimensional structure, thereby obtaining a solid electrolyte sheet in which the interior of the three-dimensional structure is filled with the second solid electrolyte layer; The method for producing a solid electrolyte sheet comprising the steps of:

[0009] In the method for producing a solid electrolyte sheet of the present invention, a sheet-like three-dimensional structure is inserted into a second uncured material of a second slurry containing a solid electrolyte, and the second uncured material that has entered the interior of the three-dimensional structure and the second uncured material on the three-dimensional structure are dried to form a second solid electrolyte layer inside the three-dimensional structure and on the three-dimensional structure, thereby obtaining a solid electrolyte sheet in which the second solid electrolyte layer is filled inside the three-dimensional structure, thereby suppressing wrinkles in the three-dimensional structure and air bubbles along them, and also suppressing breakage of the three-dimensional structure.

[0010] [2] The method for producing a solid electrolyte sheet according to [1], wherein in the fourth step, the three-dimensional structure is allowed to penetrate into the second uncured material up to a surface of the first solid electrolyte layer.

[0011] In the method for producing a solid electrolyte sheet of the present invention, in the fourth step, the three-dimensional structure is caused to penetrate into the second uncured material up to the surface of the first solid electrolyte layer, so that the three-dimensional structure can be positioned.

[0012] [3] The method for producing a solid electrolyte sheet according to [1], wherein the three-dimensional structure is a nonwoven fabric.

[0013] The method for producing a solid electrolyte sheet of the present invention can suppress wrinkles in the nonwoven fabric and air bubbles along the wrinkles, as well as breakage of the nonwoven fabric, even when the nonwoven fabric is used as the three-dimensional structure. Effect of the Invention

[0014] According to the present invention, it is possible to provide a method for manufacturing a solid electrolyte sheet that suppresses wrinkles in a three-dimensional structure such as a nonwoven fabric and air bubbles along the wrinkles, and also suppresses breakage of the three-dimensional structure. [Brief description of the drawings]

[0015] [Figure 1] 3A to 3C are cross-sectional views showing a method for manufacturing a solid electrolyte sheet according to an embodiment of the present invention. [Diagram 2] 3A to 3C are cross-sectional views showing a method for manufacturing a solid electrolyte sheet according to an embodiment of the present invention. [Diagram 3] 3A to 3C are cross-sectional views showing a method for manufacturing a solid electrolyte sheet according to an embodiment of the present invention. [Figure 4] 3A to 3C are cross-sectional views showing a method for manufacturing a solid electrolyte sheet according to an embodiment of the present invention. [Diagram 5] FIG. 1 is a cross-sectional view showing a solid electrolyte sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0017] [Method of manufacturing solid electrolyte sheet] 1 to 4 are schematic cross-sectional views showing a method for producing a solid electrolyte sheet according to an embodiment of the present invention. A manufacturing method of a solid electrolyte sheet according to the present embodiment is a manufacturing method of a solid electrolyte sheet filled with a solid electrolyte, and includes a first step of applying a first slurry containing a solid electrolyte onto a substrate to form a first uncured material made of the first slurry, a second step of drying the first uncured material on the substrate to form a first solid electrolyte layer, a third step of applying a second slurry onto an upper surface of the first solid electrolyte layer to form a second uncured material made of the second slurry, a fourth step of allowing a sheet-like three-dimensional structure to penetrate into the second uncured material up to the surface of the first solid electrolyte layer, and a fifth step of drying the second uncured material that has penetrated into the three-dimensional structure and the second uncured material on the three-dimensional structure to form a second solid electrolyte layer inside the three-dimensional structure and on the three-dimensional structure, thereby obtaining a solid electrolyte sheet in which the second solid electrolyte layer is filled inside the three-dimensional structure.

[0018] The method for manufacturing a solid electrolyte sheet according to this embodiment includes the above-mentioned first to fifth steps, thereby manufacturing a sheet material filled with a solid electrolyte, which is formed by impregnating a three-dimensional structure with a slurry of the solid electrolyte.

[0019] "1st process" The first step is a step of applying a first slurry 2 containing a solid electrolyte onto a substrate 1 to form a first uncured material 3 made of the first slurry 2 (see FIG. 1). The first uncured material 3 is made of the first slurry 2 containing a solid electrolyte, and becomes a first solid electrolyte layer 4 when dried, which is a so-called precursor of a solid electrolyte layer. In the method for producing a solid electrolyte sheet according to the present embodiment, the first slurry 2 containing a solid electrolyte is applied onto a peelable substrate 1. A known method can be adopted as a method for applying the first slurry 2 containing a solid electrolyte. Examples of the method for applying the first slurry 2 include a blade coating method, a spraying method, and a sputtering method. The coating thickness of the first slurry containing a solid electrolyte is preferably 2.0 to 4.5 times the thickness of the solid electrolyte sheet after pressing.

[0020] The substrate 1 used in the method for producing a solid electrolyte sheet according to the present embodiment is preferably a substrate having good peeling properties with respect to the first solid electrolyte layer 4. In addition, the substrate 1 having good peeling properties with respect to the first solid electrolyte layer 4 is preferably a substrate having heat resistance to such an extent that it is not deformed or damaged by heat during the drying steps of the first slurry 2 containing the solid electrolyte, which are carried out in the second and fifth steps.

[0021] The first slurry 2 containing a solid electrolyte is not particularly limited, and may be any slurry containing at least a solid electrolyte capable of conducting lithium ions between the positive electrode and the negative electrode. For example, such a solid electrolyte may be an oxide-based electrolyte or a sulfide-based electrolyte. If necessary, the first slurry 2 containing a solid electrolyte may contain other components such as a binder. In addition, when the first slurry 2 containing a solid electrolyte further contains an electrode active material, it can be applied to a method for producing an electrode layer.

[0022] The first slurry 2 containing the solid electrolyte preferably contains lithium element, which can enhance lithium ion conductivity.

[0023] Specifically, the solid electrolyte is preferably a material containing at least lithium sulfide and at least one compound selected from the group consisting of silicon sulfide, phosphorus sulfide, and boron sulfide as a second component, and Li2S-P2S5 is particularly preferred. Such sulfide-based solid electrolytes are known to have higher lithium ion conductivity than other inorganic compounds, and may contain sulfides such as SiS2, GeS2, and B2S3 in addition to Li2S-P2S5. Furthermore, Li3PO4, halogens, halogen compounds, and the like may be added to the solid electrolyte as appropriate.

[0024] The solid electrolyte may contain a lithium ion conductor made of an inorganic compound as an inorganic solid electrolyte. Examples of the lithium ion conductor include Li3N, LISICON, and LIPON (Li 3+y PO 4- x N x ), Thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2O-Al2O3-TiO2-P2O5 (LATP).

[0025] The solid electrolyte may have any structure, such as amorphous, glassy, ​​or crystalline (crystallized glass). When the solid electrolyte is a sulfide-based solid electrolyte made of Li2S-P2S5, the lithium ion conductivity of the amorphous body is 10 -4 Scm -1 On the other hand, the lithium ion conductivity of the crystalline material is 10 -3 Scm -1 It is.

[0026] The solid electrolyte used in the method for producing a solid electrolyte sheet according to the present embodiment preferably contains at least one of phosphorus and sulfur. When the solid electrolyte further contains at least one of phosphorus and sulfur, the ionic conductivity of the resulting solid electrolyte sheet can be improved.

[0027] "Second process" The second step is a step of forming a first solid electrolyte layer 4 by drying a first uncured material 3 made of a first slurry 2 containing a solid electrolyte coated on a substrate 1 using a drying device (see FIG. 1).

[0028] As a method for forming the first solid electrolyte layer 4 by drying the first uncured material 3 made of the first slurry 2 containing a solid electrolyte applied on the substrate 1, any drying method that does not lose the shape of the slurry containing a solid electrolyte applied in a thin film form when heated may be used, and a known method may be adopted. For example, there may be mentioned a method in which the substrate 1 and the first slurry 2 containing a solid electrolyte applied on the substrate 1 (first uncured material 3) are placed on a hot plate and heated to dry the first slurry 2 containing a solid electrolyte (first uncured material 3), and a method in which an electric furnace or other known drying device is used instead of a hot plate.

[0029] "3rd process" The third step is a step of applying a second slurry 5 to the upper surface of the first solid electrolyte layer 4 formed in the second step to form a second uncured material 6 made of the second slurry 5 (see FIG. 2). The second uncured material 6 is made of the second slurry 5 containing a solid electrolyte, and is a so-called precursor of the solid electrolyte layer, which becomes the second solid electrolyte layer when dried. In the manufacturing method of the solid electrolyte sheet according to the present embodiment, the second slurry 5 containing a solid electrolyte is applied to the upper surface of the first solid electrolyte layer 4. The same method as in the first step can be used as a method for applying the second slurry 5 containing a solid electrolyte. The coating thickness of the slurry containing a solid electrolyte is preferably 2.0 to 4.5 times the thickness of the solid electrolyte sheet after pressing. The second slurry 5 may be the same as or different from the first slurry 2. When the second slurry 5 is different from the first slurry 2, for example, a slurry that easily penetrates into the three-dimensional structure 7 described later is used.

[0030] "4th process" The fourth step is a step of making the sheet-like three-dimensional structure 7 penetrate into the second uncured material 6 formed in the second step (see FIG. 3). A known method can be adopted as a method of making the three-dimensional structure 7 penetrate into the second uncured material 6. For example, a method of placing the three-dimensional structure 7 on the upper surface of the second uncured material 6 and making the three-dimensional structure 7 penetrate into the second uncured material 6 by its own weight can be exemplified. Alternatively, a method of making the three-dimensional structure 7 actively penetrate into the second uncured material 6 by bringing the laminate consisting of the base material 1, the first solid electrolyte layer 4, and the second uncured material 6 shown in FIG. 3 into contact with the three-dimensional structure 7 against a conveying roll can be exemplified. In the fourth step, it is preferable to make the sheet-like three-dimensional structure 7 penetrate into the surface of the first solid electrolyte layer 4. This allows the three-dimensional structure 7 to be positioned.

[0031] The three-dimensional structure 7 used in the manufacturing method of the solid electrolyte sheet according to the present embodiment may be, for example, a mesh, a woven fabric, a nonwoven fabric, an embossed body, a punched body, an expanded body, a foamed body, etc., and is preferably a nonwoven fabric. If the three-dimensional structure 7 is a nonwoven fabric, the three-dimensional structure 7 can be rapidly impregnated with the solid electrolyte slurry in the manufacturing method of the solid electrolyte sheet according to the present embodiment, which makes it easier to reduce the manufacturing cost related to the impregnation.

[0032] The material of the three-dimensional structure 7 is not particularly limited, and may be any sheet material capable of forming a self-supporting solid electrolyte sheet. Examples include polyethylene terephthalate, nylon, aramid, alumina (Al2O3), glass, metal, and the like. In this case, when a non-conductive material such as polyethylene terephthalate, nylon, aramid, alumina, or glass is used as the material of the three-dimensional structure 7, the method can be applied to the manufacturing method of the solid electrolyte sheet. In addition, when a conductive material such as a metal material is used as the material of the three-dimensional structure 7, the method can be applied to the manufacturing method of the electrode layer.

[0033] The porosity of the three-dimensional structure 7 is preferably 60% to 95%, more preferably 70% to 90%, and further preferably 80% to 90%.

[0034] The thickness of the three-dimensional structure 7 is preferably 5 μm to 30 μm. The thickness of the three-dimensional structure 7 is more preferably 5 μm to 20 μm, and further preferably 10 μm to 20 μm. If the thickness of the three-dimensional structure 7 is less than 5 μm, there is a risk of short-circuiting between electrodes when a battery is formed. On the other hand, if the thickness of the three-dimensional structure 7 exceeds 30 μm, it becomes difficult to apply a solid electrolyte slurry to the three-dimensional structure 7, making it difficult to realize a solid electrolyte sheet with high energy density.

[0035] [5th ​​step] The fifth step is a step of drying the second uncured material 6 that has entered the inside of the three-dimensional structure 7 and the second uncured material 6 on the three-dimensional structure 7 to form a second solid electrolyte layer 8 inside the three-dimensional structure 7 and on the three-dimensional structure 7. This step is a step of filling the inside of the three-dimensional structure 7 with the second solid electrolyte layer 8 and obtaining a solid electrolyte sheet 10 in which the first solid electrolyte layer 4 and the second solid electrolyte layer 8 are integrated (see FIG. 4).

[0036] As a method for forming the second solid electrolyte layer 8 by drying the second uncured material 6 that has penetrated inside the three-dimensional structure 7 and the second uncured material 6 on the three-dimensional structure 7, any drying method that does not cause the shape of the slurry containing the solid electrolyte applied in a thin film to collapse when heated can be used, as in the second process, and any known method can be used.

[0037] After drying in the fifth step, the peelable substrate may or may not be peeled off from the solid electrolyte sheet obtained until it is used as a battery component in the manufacture of a solid battery. After pressing the solid electrolyte sheet, a positive electrode layer, a solid electrolyte sheet, and a negative electrode layer are laminated in this order and pressed to manufacture a solid battery. A solid battery can also be manufactured by laminating the positive electrode layer, the solid electrolyte sheet, and the negative electrode layer in this order and pressing.

[0038] According to the method for manufacturing a solid electrolyte sheet according to the present embodiment, the three-dimensional structure 7 can be disposed at any position in the thickness direction of the solid electrolyte sheet 10 by adjusting the thickness of the first uncured material 3 and the thickness of the second uncured material 6.

[0039] The method for producing a solid electrolyte sheet of the present invention can be applied to the above-mentioned method for producing a solid electrolyte sheet, and can also be applied to a method for producing a sheet material containing a solid electrolyte, such as an electrode layer, by making various additions, modifications, or deletions within a scope that does not deviate from the spirit of the invention.

[0040] [Solid electrolyte sheet] A solid electrolyte sheet according to an embodiment of the present invention includes a sheet-like three-dimensional structure filled with a solid electrolyte, and a solid electrolyte layer formed so as to cover the front and back surfaces of the three-dimensional structure. More specifically, the solid electrolyte sheet according to this embodiment is a solid electrolyte sheet manufactured by the manufacturing method for a solid electrolyte sheet according to this embodiment described above. For the solid electrolyte layer and the three-dimensional structure, an electrode material that can be used in the manufacturing method for a solid electrolyte sheet described above can be preferably used.

[0041] FIG. 5 is a cross-sectional view showing a solid electrolyte sheet according to the present embodiment. As shown in Fig. 5, the solid electrolyte sheet 100 according to the present embodiment includes, for example, a sheet-like three-dimensional structure 110 disposed at approximately the center in the thickness direction and filled with a solid electrolyte, and a solid electrolyte layer 120 formed to cover the front and back surfaces of the three-dimensional structure 110. Therefore, when the solid electrolyte sheet 100 is applied to a solid-state battery, lithium ions moving from the positive electrode to the negative electrode can move along the three-dimensional structure 110 at approximately the center in the thickness direction, so that the movement is not significantly hindered and the movement speed is not significantly reduced. As a result, the insertion and desorption of lithium ions into and from the electrodes is performed more smoothly than in the past, and the output performance of the battery is improved.

[0042] Therefore, according to the manufacturing method of the solid electrolyte sheet and the solid electrolyte sheet according to the present embodiment, lithium ions can be smoothly inserted and removed from the solid electrolyte layer to the electrode, thereby improving the battery output performance, and the adhesiveness between the solid electrolyte layer and the electrode layer can be improved, thereby suppressing interfacial peeling and short-circuiting between the solid electrolyte layer and the electrode layer.

[0043] The solid electrolyte sheet of the present embodiment can be applied to a solid-state battery as a solid electrolyte layer by pressing.

[0044] The present invention is not limited to the above-described embodiment, and the present invention includes modifications and improvements within the scope that can achieve the object of the present invention. [Explanation of symbols]

[0045] 1 Base material 2. First Slurry 3 First uncured material 4 First solid electrolyte layer 5. Second Slurry 6 Second uncured material 7 Three-dimensional structure 8 Second solid electrolyte layer 10 Solid electrolyte sheet

Claims

1. A method for producing a solid electrolyte sheet filled with a solid electrolyte, comprising the steps of: A first step of applying a first slurry containing a solid electrolyte onto a substrate to form a first uncured material made of the first slurry; a second step of drying the first uncured material on the substrate to form a first solid electrolyte layer; a third step of applying a second slurry to an upper surface of the first solid electrolyte layer to form a second uncured material made of the second slurry; A fourth step of penetrating a sheet-like three-dimensional structure into the second uncured material; a fifth step of drying the second uncured material that has entered the interior of the three-dimensional structure and the second uncured material on the three-dimensional structure to form a second solid electrolyte layer inside the three-dimensional structure and on the three-dimensional structure, thereby obtaining a solid electrolyte sheet in which the interior of the three-dimensional structure is filled with the second solid electrolyte layer; The method for producing a solid electrolyte sheet comprising the steps of:

2. 2 . The method for producing a solid electrolyte sheet according to claim 1 , wherein in the fourth step, the three-dimensional structure is caused to penetrate into the second uncured material up to a surface of the first solid electrolyte layer.

3. The method for producing a solid electrolyte sheet according to claim 1 , wherein the three-dimensional structure is a nonwoven fabric.

Citation Information

Patent Citations

  • Solid electrolyte carrying nonwoven fabric and solid electrolyte sheet

    JP2020024860A

  • Pseudo solid electrolyte layer and manufacturing method thereof

    JP2020038761A

  • Method for manufacturing solid-state battery sheet and method for manufacturing laminate to be used for the same

    JP2021163759A

  • Method of manufacturing solid electrolyte sheet, and solid electrolyte sheet

    JP2022151241A

  • Modified solid electrolyte membrane, its manufacturing method, and lithium battery

    JP2022506297A